Ubiquitin signaling in pancreatic ductal adenocarcinoma - Lv, Shengnan; Zhang, Jian; Peng, Xinyu; Liu, Huan; Liu, Yan; Wei, Feng (Frontiers in Molecular Biosciences, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignant tumor of digestive system, ascribed to its rapid progression and prone to metastasis. Few effective treatment is available and its fiveyear survival rate is less than 9%. Many cell biological and signaling events are involved in the development of PDAC, among which protein post-translational modification (PTMs) such as ubiquitination plays crucial roles. Catalyzed mostly by a three-enzyme cascade, ubiquitination induces changes in protein activity mainly by altering their stability in PDAC. Due to their role in substrate recognition, E3 ubiquitin ligases (E3s) dictate the outcome of the modification. Ubiquitination can be reversed by deubiquitylases (DUBs) which return modified proteins to their native form. Dysregulations of E3s or DUBs that disrupt protein homeostasis are involved in PDAC. Moreover, the ubiquitination system has been exploited to develop therapeutic strategies such as proteolysis targeting chimeras (PROTACs). In this review, we summarize recent progress in our understanding of the role of ubiquitination in the development of PDAC and offer perspectives in the design of new therapies against this highly challenging disease.